Identification of drivers of mycobacterial resistance to peptidoglycan synthesis inhibitors - Olivença, Francisco; Ferreira, Cláudia; Nunes, Alexandra; Silveiro, Cátia; Pimentel, Madalena; Gomes, João Paulo; Catalão, Maria João (Frontiers in Microbiology, 2022)
Beta-lactams have been excluded from tuberculosis therapy due to the intrinsic resistance of Mycobacterium tuberculosis (Mtb) to this antibiotic class, usually attributed to a potent beta-lactamase, BlaC, and to an unusually complex cell wall. In this pathogen, the peptidoglycan is cross-linked by penicillin-binding proteins (PBPs) and L,D-transpeptidases, the latter resistant to inhibition by most beta-lactams. However, recent studies have shown encouraging results of beta-lactam/beta-lactamase inhibitor combinations in clinical strains. Additional research on the mechanisms of action and resistance to these antibiotics and other inhibitors of peptidoglycan synthesis, such as the glycopeptides, is crucial to ascertain their place in alternative regimens against drug-resistant strains. Within this scope, we applied selective pressure to generate mutants resistant to amoxicillin, meropenem or vancomycin in Mtb H37Rv or Mycolicibacterium smegmatis (Msm) mc2-155. These were phenotypically characterized and whole-genome sequencing was performed. Mutations in promising targets or orthologue genes were inspected in Mtb clinical strains to establish potential associations between altered susceptibility to beta-lactams and presence of key genomic signatures. The obtained isolates had substantial increases in the minimum inhibitory concentration of the selection antibiotic and beta-lactam cross-resistance was detected in Mtb. Mutations in L,D-transpeptidases and major PBPs, canonical targets, or BlaC were not found. The transcriptional regulator PhoP (Rv0757) emerged as a common denominator for Mtb resistance to both amoxicillin and meropenem, while Rv2864c, a lipoprotein with PBP activity, appears to be specifically involved in decreased susceptibility to the carbapenem. Nonetheless, the mutational pattern detected in meropenem-resistant mutants was different from the yielded by amoxicillin- or vancomycin-selected isolates, suggesting that distinct pathways may participate in increased resistance to peptidoglycan inhibitors, including at the level of beta-lactam subclasses. Cross-resistance between beta-lactams and antimycobacterials was mostly unnoticed and Msm meropenem-resistant mutants from parental strains with previous resistance to isoniazid or ethambutol were isolated at a lower frequency. Although cell-associated nitrocefin hydrolysis was increased in some of the isolates, our findings suggest that traditional assumptions of Mtb resistance relying largely in beta-lactamase activity and impaired access of hydrophilic molecules through lipid-rich outer layers should be challenged. Moreover, the therapeutical potential of the identified Mtb targets should be explored.